Out of Time: The Experience of Contrasting Temporal Frameworks in Participatory Art - Vilstrup Holm, Ditte (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Participatory art turns the artwork into a process of engagement and co-creation, and it thus involves forms of time-based coordination that influence the experience of creating participatory art. In this paper I argue that participatory art is underscored by two contrasting temporal frameworks. One is the framework of long-term durational approaches that have been internalized among artists as an ethical and political obligation toward participants; the other is the short-term temporary framework that typically comes with project funding and steers the project toward delivery of target outcomes. To show the tensions to which these contrasting temporal frameworks can give rise, I analyze the development of a participatory art project in Copenhagen’s South Harbor. Specifically, the analysis emphasizes how tensions arose in respect to delimitations of project aspects such as who constitutes the creative team, what is the task before us, and what is our expected contribution to the community. By emphasizing the tensions arising from contrasting temporal frameworks, the article contributes to a more nuanced understanding of the experience of creating participatory art, and to problematizing the question of time for participatory art.